Rancang Bangun Aplikasi Penentuan Menu Makanan Ibu Hamil Menggunakan Metode Cooper - Surya Atmaja, I Gusti Bagus Ngurah; Wibowo, Januar; Sudarmaningtyas, Pantjawati (Jurnal JSIKA, 2012)
The death level of pregnant mother in Indonesia is the highest level in ASEAN countries, approximately 19.000 death every years or 4000 death every 100.000 birthing. Many factors cause that high level of death, like deseases or nutrient lack.In this final project, will do the calculation of nutrient that refers weight, height, age of womb, activity level, and total of sleep hours. With the support of Coopper method, this calculation will produce a good result food menu.   Keywords: nutrition of pregnant women, food menu, Cooper Method.